Biological effects of cold and its use in sport - Ewelina Litwa; Anna Dobosiewicz; Gracjan Różański; Nataliia Badiuk (Nicolaus Copernicus University in Toruń, Poland - University Sports Center, 2020)
Using the cold properly can have many health benefits. The impact of cold on the human body is multidimensional and affects various systems and organs. Cold has found its application in medicine, sport, biological regeneration and physical recreation in the form of cold baths.